2023
DOI: 10.1038/s42003-023-04534-6
|View full text |Cite|
|
Sign up to set email alerts
|

The AP-1 transcription factor Fosl-2 drives cardiac fibrosis and arrhythmias under immunofibrotic conditions

Abstract: Fibrotic changes in the myocardium and cardiac arrhythmias represent fatal complications in systemic sclerosis (SSc), however the underlying mechanisms remain elusive. Mice overexpressing transcription factor Fosl-2 (Fosl-2tg) represent animal model of SSc. Fosl-2tg mice showed interstitial cardiac fibrosis, disorganized connexin-43/40 in intercalated discs and deregulated expression of genes controlling conduction system, and developed higher heart rate (HR), prolonged QT intervals, arrhythmias with prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There is only one previous study that analyzed the association between Cxs and fibrosis related to SSc [ 43 ]. In their study, Stellato et al analyzed the myocardium of a Fosl-2-overexpressing mouse model of SSc and found disorganized distribution of both Cx40 and Cx43 in the myocardium of the SSc model compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one previous study that analyzed the association between Cxs and fibrosis related to SSc [ 43 ]. In their study, Stellato et al analyzed the myocardium of a Fosl-2-overexpressing mouse model of SSc and found disorganized distribution of both Cx40 and Cx43 in the myocardium of the SSc model compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…These genes belong to the activator protein-1 (AP-1) transcription factor family, which is important for cardiomyocyte stress responses, cardiac inflammation and fibrosis. 31,32 Notably, the STAT3 binding motif was also highly enriched.…”
Section: Atac-seq Highlights Ap-1 Family Genesmentioning
confidence: 99%
“…The powerful enrichment of the AP-1 family of transcription factors following rmIL11 injection, seen in bulk RNA-seq, snRNA-seq and ATAC-seq was unexpected and likely has detrimental effects in the mouse heart 31,37 . AP-1 family activation is not immediately downstream of IL11:IL11RA:gp130 signalling and thus, the early IL11-stimulated activation of JAK/STAT3 likely primes CMs to upregulate, activate and respond to AP-1 transcription factors.…”
Section: Jak Inhibition Protects Against Il11-induced Cardiac Dysfunc...mentioning
confidence: 99%